THE VIDEO OF “SUMPING” (HUSBANDS’ SUPPORT ACCOMPANY) ON HUSBANDS’ MOTIVATION IN ACCOMPANYING THE CHILDBIRTH IN ISLAND AREA - Utami Dewi; Rahmadona Rahmadona; Nurniati Tianastia Rullyni (Bajang Institute, 2022)
Reducing the incidence of childbirth complications requires the role of the family (especially the husband). Besides, the improvement of husbands' participation in reproductive health is to provide husbands with information and to include husbands in every effort to improve reproductive health. One of the activities that husbands can do to improve the health of mothers and children is to accompany their wives during the delivery process. The design of this study was quasi-experimental with a post-test-only control group design. In addition, the treatment given to the respondents was a video